Resignifying 'responsibility': India, exceptionalism and nuclear non-proliferation. Issue 3 (2nd September 2018) - Chacko, Priya; Davis, Alexander E
ABSTRACT: Postcolonial scholarship on nuclear weapons has demonstrated that mainstream literature perpetuates a set of orientalist discourses about 'Enlightenment' and 'civilization' which legitimizes global hierarchies. What has been less studied is the role of non-Western countries in challenging or perpetuating these discourses. This article focuses on the discourse of 'nuclear responsibility' as it has been deployed by Indian official to challenge Western discourses of nuclear responsibility that are linked to the Nuclear Non-Proliferation Treaty (NPT). Using Judith Butler's concept of resignification, we argue that India has sought to resignify the Western discourse of nuclear responsibility such that it is linked to nuclear disarmament and equality rather than nuclear non-proliferation and hierarchy. In its discourse on nuclear responsibility, India's status as a responsible nuclear power is based, not on its compliance with international regimes or norms, but on its 'civilizational exceptionalism'. We argue that resignification is a form of non-western agency but is highly circumscribed. Its success has been dependent upon the broader global political context and has been limited to moving India up the global nuclear hierarchy rather than challenging the hierarchy itself.